PENGARUH EKSTRAK ETANOL BUAH LABU SIAM (SECHIUM EDULE JACQ.SWARTZ.) TERHADAP KADAR INTERLEUKIN 6 DAN HISTOPATOLOGI PANKREAS MENCIT HIPERGLIKEMIA YANG DIINDUKSI STREPTOZOTOCIN (STZ) - Paska Ramawati Situmorang (Elisabeth Health Jurnal, 2017)
Diabetes mellitus now becomes a global serious theat with continues encreasingly prevalence. Ethanol extract of squash fruit Chayotte (Sechium edule) is a plant that contains flavonoidsareanti-inflammatory. The objective of this study was to determine the effect of ethanol extract of Squash fruit Chayotte (Sechium edule) to Interleukin 6 level and increasedthe size ofthe diameter of the pancreas in STZ-induced hyperglycemic mice model. Goals : This research is experimental research uses Post test randomized controlled group design upon male mice, and divided into 4 groups; negative control group, positive control group is treated with streptozotocin at a dose of 60 mg/kg weight, and groups of therapy (dosage 100 gram/kg weight, 200 gram/kg weight). Methods : The measurement of the level interleleukin 6 (IL-6) used ELISA method and the description of histopatoligy pancreas. The data analysis of level IL-6 level uses One Way ANOVA (α = 0,005) and pancreas histology image used descriptive analysis. Result : The results showed a decrease in the levels of IL-6, although not significant if it’s compared to the positive control. The preparat histopathology pancreas observation increased diameter which showed widening of cell β of pancreas. Conclution : The conclusion of this research was that ethanol extract of squash fruit can reduce levels IL-6 and prevent the hiperglikemia mice pancreas damages